Implementation of Multihoming Border Gateway Protocol for Internet Connection of Two Internet Service Providers - Alfian Ari Putra; Sumarno (Procedia of Engineering and Life Science, 2021)
Today the internet is inseparable in the life of modern society. For this reason, fast and reliable internet is very important. To achieve this, on the internet there are various kinds of technologies that make it very reliable. One of the technologies used in the internet is the Multihoming Border Gateway Protocol (BGP). This BGP technology allows every router on the internet to be connected and exchange routing information needed on the internet. BGP Multihoming allows two or more Autonomous Systems (AS) to connect and exchange routing information without any routing information being wrong. So if there is one AS experiencing interference then it will not significantly affect the other AS. That is because there are two or more pathways that can be traversed to get to the destination AS.